Nrf2 Is a Key Regulator on Puerarin Preventing Cardiac Fibrosis and Upregulating Metabolic Enzymes UGT1A1 in Rats - Cai, Shao-Ai; Hou, Ning; Zhao, Gan-Jian; Liu, Xia-Wen; He, Ying-Yan; Liu, Hai-Lin; Hua, Yong-Quan; Li, Li-Rong; Huang, Yin; Ou, Cai-Wen; Luo, Cheng-Feng; Chen, Min-Sheng (Frontiers in Pharmacology, 2018)
Puerarin is an isoflavone isolated from Radix puerariae. Emerging evidence shown that puerarin possesses therapeutic benefits that aid in the prevention of cardiovascular diseases. In this study, we evaluated the effects of puerarin on oxidative stress and cardiac fibrosis induced by abdominal aortic banding (AB) and angiotensin II (AngII). We also investigated the mechanisms underlying this phenomenon. The results of histopathological analysis, as well as measurements of collagen expression and cardiac fibroblast proliferation indicated that puerarin administration significantly inhibited cardiac fibrosis induced by AB and AngII. These effects of puerarin may reflect activation of Nrf2/ROS pathway. This hypothesis is supported by observed decreases of reactive oxygen species (ROS), decreases Keap 1, increases Nrf2 expression and nuclear translocation, and decreases of collagen expressions in cardiac fibroblasts treated with a combination of puerarin and AngII. Inhibition of Nrf2 with specific Nrf2 siRNA or Nrf2 inhibitor brusatol attenuated anti-fibrotic and anti-oxidant effects of puerarin. The metabolic effects of puerarin were mediated by Nrf2 through upregulation of UDP-glucuronosyltransferase (UGT) 1A1. The Nrf2 agonist tBHQ upregulated protein expression of UGT1A1 over time in cardiac fibroblasts. Treatment with Nrf2 siRNA or brusatol dramatically decreased UGT1A1 expression in puerarin-treated fibroblasts. The results of chromatin immunoprecipitation–qPCR further confirmed that puerarin significantly increased binding of Nrf2 to the promoter region of UGT1A1. Western blot analysis showed that puerarin significantly inhibited AngII-induced phosphorylation of p38. A specific inhibitor of p38, SB203580, decreased collagen expression, and ROS generation induced by AngII in cardiac fibroblast. Together, these results suggest that puerarin prevents cardiac fibrosis via activation of Nrf2 and inactivation of p38-MAPK. Nrf2 is the key regulator of anti-fibrotic effects and upregulates metabolic enzymes UGT1A1. Autoregulatory circuits between puerarin and Nrf2-regulated UGT1A1 attenuates side effects associated with treatment, but it does not weaken puerarin’s pharmacological effects.